2010
DOI: 10.1186/1749-8090-5-21
|View full text |Cite
|
Sign up to set email alerts
|

A novel and safe technique in closed tube thoracostomy

Abstract: BackgroundTube thoracostomy (TT) is the most commonly performed surgical procedure in thoracic surgery clinics. The procedure might have to be repeated due to ineffective drainage in patients with tube malposition (TM), in whom the drain is not directed to the apex or located in the fissure. Trocar technique, which is used to prevent TM, is not recommended because of its potential for severe complications.MethodsThe study involved 180 patients who required TT application for any etiology within one year. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 7 publications
(6 reference statements)
0
21
0
2
Order By: Relevance
“…However, Grosse-Wortmann et al (2010) reported peak prevalence of arrhythmias 79.1%, which was higher than all other reported studies. They explained this difference as being a result of Holter monitoring, which may reflect a more sensitive method of detection, especially of extrasystoles, instead of bedside monitoring [ 13 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Grosse-Wortmann et al (2010) reported peak prevalence of arrhythmias 79.1%, which was higher than all other reported studies. They explained this difference as being a result of Holter monitoring, which may reflect a more sensitive method of detection, especially of extrasystoles, instead of bedside monitoring [ 13 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other indications for tube thoracostomy in this study were hydropneumothorax (17%), empyema /parapneumonic effusion (9%) & malignant pleural effusion (7%). Aylwin CJ et al [9] and Miller KS et al [10] [11,12,13]. almost all the patients showed ECG changes (ischemic changes, tachycardia, arrhythmia) commonly encountered in Pneumothorax (19.4%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tüp torakostomi işleminin genel uygulayıcıları göğüs cerrahları olmakla beraber, son yıllarda tüp torakostomi işlemi acil tıp uzmanlığı gibi başka uzmanlıklar tarafından da uygulanmaktadır (19,20) . Bu durum özel-likle acil servislere başvuran travma ve spontan pnö-motoraks hastalarına erken müdahaleyi sağlamakta-dır.…”
Section: Discussionunclassified